For the sake of a liberalized Romanian culture! What about an interdisciplinary and transdisciplinary canon instead of the isolated monopolies with a subscription to the state budget? - Felix Narcis Nicolau (Swedish Journal of Romanian Studies, 2020)
Fake canonizations are prevalent in the former communist countries wherein arts and culture in general may still function as propaganda weaponry at the hands of the sponsoring state. The public is almost eliminated from the process of canonization, as the publishing houses, art galleries, and cultural industries seldom survive and flourish from sales to a real public. As a rule, their rarefied public is summoned from a flimsy contingent, from the less promoted artists who try thus to conjure the benevolence of the critics and famed authors/artists, and from those who are ready to attend cultural events as long as they are financially covered by the state. For instance, a sizable percent of the funds directed towards literature from the state budget in Romania has been constantly invested in the promotion of Mircea Cărtărescu in the vain hope (so far) the Romanian literature will be awarded the Nobel Prize for literature and will cure thus a profusely nourished complex of inferiority. Maybe in the new future. Meanwhile, many more modern and impactful writers simply vanish into the abyss of anonymity as the bookshops are interested in promoting only those writers coming from publishing houses with a subscription to the state budget. This would be one explanation for the constant decrease in the public paying for literary and artistic works. The result of an haphazard process of canonization and of the lack of a free cultural market (at least 50% of investments coming from private sources) are obvious. Wherefrom the impending need of an interdisciplinary and transdisciplinary super-arch-canon.